2018
DOI: 10.1364/oe.26.010509
|View full text |Cite
|
Sign up to set email alerts
|

Double-hump solitons in fractional dimensions with a đ’«đ’Żâ€“symmetric potential

Abstract: We investigate the properties of double-hump solitons supported by the nonlinear Schrödinger equation featuring a combination of parity-time symmetry and fractional-order diffraction effect. Two classes of nonlinear states, i.e., out-of-phase and in-phase solitons are found. Each class contains two families of solitons originating from the same linear mode in both focusing and defocusing nonlinear Kerr media. The critical phase-transition point increases monotonously with increasing LĂ©vy index. For strong gain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Since then, interesting results on generating and manipulating linear and nonlinear propagation dynamics of laser beams in such fractional optical models were obtained. Some typical works include: Gaus- * zengjh@opt.ac.cn sian beams either evolved into diffraction-free beams [14] or undergone conical diffraction [15] during propagation without a potential, PT symmetry [16] and propagation dynamics of the super-Gaussian beams [17] , optical beams propagation with a harmonic potential [14,15,17] (which supports spatiotemporal accessible solitons too [18,19]) and periodic potentials [16,20], propagation management of light beams in a double-barrier potential [21], in the context of linear FSE regime; and in terms of nonlinear fractional Schrödinger equation (NLFSE) regime [22][23][24][25][26][27][28], including optical solitons (or solitary waves) without external potential [23,24], solitons supported by linear [25][26][27] and nonlinear [28] periodic potentials which refer, respectively, to optical lattice and nonlinear lattice as described below.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, interesting results on generating and manipulating linear and nonlinear propagation dynamics of laser beams in such fractional optical models were obtained. Some typical works include: Gaus- * zengjh@opt.ac.cn sian beams either evolved into diffraction-free beams [14] or undergone conical diffraction [15] during propagation without a potential, PT symmetry [16] and propagation dynamics of the super-Gaussian beams [17] , optical beams propagation with a harmonic potential [14,15,17] (which supports spatiotemporal accessible solitons too [18,19]) and periodic potentials [16,20], propagation management of light beams in a double-barrier potential [21], in the context of linear FSE regime; and in terms of nonlinear fractional Schrödinger equation (NLFSE) regime [22][23][24][25][26][27][28], including optical solitons (or solitary waves) without external potential [23,24], solitons supported by linear [25][26][27] and nonlinear [28] periodic potentials which refer, respectively, to optical lattice and nonlinear lattice as described below.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, PT symmetry in the spatial FSE was reported by Zhang et al, who showed that the nondiffracting propagation and conical diffraction of input beams were found at the critical point of a PT-symmetric lattice [26]. More recently, Dong et al have investigated double-hump solitons in the 1D NFSE with PT-symmetric potentials, and they found that the out-of-phase and in-phase solitons can be stable in focusing media and defocusing media, respectively [27]. Up to now, neither the combination of PT symmetry and lattice nor the higher-dimension solitons in the NFSE have been reported.…”
Section: Introductionmentioning
confidence: 82%
“…Since then, a number of striking properties have been reported in model of the FSE. [27][28][29][30] When the nonlinear effects have been considered in the FSE, a variety of fractional optical solitons can be produced by NLFSEs, [31] such as spatiotemporal accessible solitons, [32,33] double-hump solitons, [34] gap solitons, [35,36] nonlocal solitons, [37] www.advancedsciencenews.com www.ann-phys.org off-site and on-site vortex solitons, [38] bright solitons under the action of periodically spatially modulated nonlinearities, [39,40] dissipative surface solitons, [41] discrete solitons, [42] asymmetric solitons, [43] as well as vortex solitons in free space. [44] Optical solitons may undergo spontaneous symmetry breaking in conventional Hermitian and parity-time symmetric NLSE, an interesting generalization is to explore the symmetry breaking bifurcations of optical solitons in the NLFSE.…”
Section: Introductionmentioning
confidence: 99%